Fibrations and cofibrations in a stratified model category - Spalinski, J. (Algebra and Discrete Mathematics, 2006)
We introduce n-acyclic cofibrations and n-acyclic
fibrations in a stratified model category and show that they have
the key properties of (acyclic) cofibrations and (acyclic) fibrations
in a model category. We analyse their action on sets of homotopy
classes and give an application to homotopy colimits and limits.